Istratijiyyat ta’allum al-qawa’ed al-nahwiyyah lada tolabat al-bakalurius bi jami’at Indonesia. - Chik, Abdul Rahman Bin Chik; Jakfar, Rozana Jakfar (IRKHS, IIUM, 2021)
An anylisis of learning strategies for Arabic syntax employed by students of Universiti Indonesia (UI) Jakarta.